FACTORS RELATED TO COMPLIANCE WITH FLUID RESTRICTION IN HEMODIALYSIS PATIENTS - Mia Ipana; Tri Hapsari Retno Agustiyowati (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
This study investigates compliance with fluid restriction in chronic kidney disease patients undergoing hemodialysis, focusing on factors like knowledge, motivation, and social support. This research is a quantitative correlational analytic study using a cross-sectional study design. Sampling used the convenience sampling method on a total of 146 respondents at the Tk II Dustira Hospital. Data were collected using a fluid restriction compliance questionnaire, a knowledge questionnaire, a Treatment Motivation Questionnaire (TMQ) motivation questionnaire and a Multidimensional Scale of Perceived Social (MSPSS) questionnaire. Data analysis using spearmen and linear regression. The results of the research using the spearmen test showed that there was a significant effect between knowledge, motivation and social support on fluid restriction compliance. Knowledge (p = 0.001, r = 0.274), motivation (p = 0.008 , r = 0.218) and social support (p = 0.005, r = 0.231). The most dominant factor influencing compliance with fluid restriction using logistic regression test is the social support factor value of 0.006. This study can be concluded that knowledge, motivation and social support have a relationship with fluid restriction compliance and the most influential factor is social support with a p-value of 0.006 and a B-value of 1.016.